Motivations, Values, and Beliefs Behind the Embracing of the Prosperity Gospel by Selected African Christian Communities: How an African Worldview encounters the teachings of the prosperity gospel in Nairobi, Kenya - Evans, Elizabeth (Tangaza University College, 2016)
This thesis examines a phenomenon of the rapid growth and proliferation of prosperity gospel churches in Nairobi. It presents field research findings which demonstrate that the attraction to churches preaching the prosperity gospel arises because those teachings resonate, subconsciously or informally, with the motivations, values, and beliefs of the African understanding of evil and in the centrality of God as the source of all blessings in daily life. The focus of the thesis was not theological and did not attempt to uncover social ills related to the prosperity gospel. This thesis used anthropological methods and was concerned with cultural influences especially in regard to the African worldview. It argued that there is a framework in the African worldview that allows the prosperity gospel to dwell. While several African scholars have asserted that the prosperity gospel attracts many Africans because of the similarities between the two, the literature regarding the link between the prosperity gospel in Nairobi and the African worldview has not been a focus in literature dealing with the Nairobi setting. This thesis focuses on the Nairobi setting and presents field data in the light of this contemporary issue facing the Church in Kenya. The research revealed that the prosperity gospel recognizes the felt need of the African to gain power in order to have a full life and to do God’s will. In the past, the failure to acknowledge the African’s belief system when many missionaries heralded the Gospel of Christ, did not allow Africans in some instances to examine their own beliefs and become integrated Christians. The prosperity gospel engages it. Moreover, it gives people an alternative to resigning themselves to their circumstances. In addition, the prosperity gospel uses the African worldview for its own purposes with the use of symbols and words that communicate deeply in the African mind even penetrating to the emotions and fitting itself either sub-consciously or informally into the African paradigm for living a successful life pleasing to God.
free